Trichosanthin cooperates with Granzyme B to restrain tumor formation in tongue squamous cell carcinoma - Zeyao Zhu; Zhenguang Ying; Meiqi Zeng; Qiang Zhang; Guiqing Liao; Yunliu Liang; Chunman Li; Chengfei Zhang; Xia Wang; Weipeng Jiang; Ping Luan; Ou Sha (BMC, 2021)
Abstract Background Tongue squamous cell carcinoma (TSCC) is a common type of oral cancer, with a relatively poor prognosis and low post-treatment survival rate. Various strategies and novel drugs to treat TSCC are emerging and under investigation. Trichosanthin (TCS), extracted from the root tubers of Tian-Hua-Fen, has been found to have multiple biological and pharmacological functions, including inhibiting the growth of cancer cells. Granzyme B (GrzB) is a common toxic protein secreted by natural killer cells and cytotoxic T cells. Our group has reported that TCS combined with GrzB might be a superior approach to inhibit liver tumor progression, but data relating to the use of this combination to treat TSCC remain limited. The aim of this study was to examine the effectiveness of TCS on TSCC processes and underlying mechanisms. Methods First, we screened the potential antitumor activity of TCS using two types of SCC cell lines. Subsequently, a subcutaneous squamous cell carcinoma xenograft model in nude mice was established. These model mice were randomly divided into four groups and treated as follows: control group, TCS treatment group, GrzB treatment group, and TCS/GrzB combination treatment group. Various tumorigenesis parameters, such as Ki67, PCNA, caspase-3, Bcl-2 and VEGFA, et al., were performed to determine the effects of these treatments on tumor development. Results Screening confirmed that the SCC25 line exhibited greater sensitivity than the SCC15 line to TCS in vitro studies. TCS or GrzB treatment significantly inhibited tumor growth compared with the inhibition seen in the control group. The TCS/GrzB combination inhibited tumor growth more than either drug alone. TCS treatment inhibited tumor proliferation by downregulating Ki67 and Bcl2 protein expression while accelerating tumor apoptosis. In the TCS/GrzB-treated group, expression of Ki67 was further downregulated, while the level of activated caspase-3 was increased, compared with their expression in either of the single drug treatment groups. Conclusion These results suggest that the TCS/GrzB combination could represent an effective immunotherapy for TSCC.